Political economy to understand the economic growth in China - Palomino Selem, Carlos (2014)
After a profile of excellence economic growth in China during the first decade of XXI century; this country is experiencing a crisis of accumulation model. This paper aims to develop a theoretical framework of a scheme employing the criteria of political economy to explain the problem which crosses the giant Asian country, the pampering that will not be solved using mainly conventional policies macroeconomic and / or monetary and so-called structural reforms required.